Circumglobal teleconnections, the Jet Stream Waveguide, and the North Atlantic Oscillation - Branstator, Grant (Grant Branstator) (authoraut); National Oceanic and Atmospheric Administration (NOAA) (funderfnd); National Aeronautics and Space Administration (NASA) (funderfnd)
National Oceanic and Atmospheric Administration (NOAA): NA16GP1015 National Aeronautics and Space Administration (NASA): S-10180-X Monthly and seasonally averaged upper-tropospheric Northern Hemisphere winter fields are examined to determine whether the waveguiding effect of the time-averaged tropospheric jets on low-frequency disturbances that is predicted by theory does affect the behavior of these disturbances. It is found that, indeed, disturbances in the vicinity of the mean jets, particularly the jet that stretches across South Asia, are fundamentally different from those that reside in regions where the mean winds have weaker meridional gradients, like the mid-Pacific. Patterns of variability in the jets tend to be smaller scale and to consist of zonally oriented chains of anomalies while variability in the mid-Pacific is composed of patterns with distinct meridional orientation. Because they are meridionally trapped and zonally elongated, patterns associated with the jet stream waveguide connect activity at points that are much farther apart than do patterns in other regions of the globe. Within the South Asian waveguide, variability tends to be composed of a zonal wave-5 feature with no favored longitudinal phase. One phase of this pattern is special in that it covaries with distant regions in midlatitudes producing a pattern of variability that circumscribes the hemisphere. This special pattern has a noticeable zonal mean component. Furthermore, it is prominent enough that for the upper troposphere it is embedded in the leading EOF of streamfunction and is essentially the same as the leading EOF of the ν wind component. Over the North Atlantic, its structure has a great deal in common with the structure of the North Atlantic Oscillation, so that its features can make significant contributions to plots of hemispheric circulation anomalies associated with that phenomenon.